Influence of breed, gender, reproductive status and origin on noise related fears in the Belgrade population of dogs - Vučinić Marijana; Radisavljević Katarina; Radeski M.; Ostović M. (Acta Veterinaria, 2013)
The prevalence of canine noise-related fears was studied by the questionnaire method of dogs’ owners from different part of Belgrade. Dog-owners (N=147) were chosen from a variety of sources (permissive municipal areas and parks for walking of dogs, dog shows and exhibitions and veterinary surgeries for small animal practice). Owners indicated noise-related fears in 59 dogs (40.14%). Twenty-six (17.69%) of them were mixed breed dogs and 33 (22.45%) were pure breed dogs. Noise-related fears were indicated in 25 females (17.01%) and in 34 (23.13%) males and, in 27 (18.37%) intact and 32 (21.77%) neutered dogs. From 59 dogs with noise-related fears 13 of them (8.84%) were directly purchased from breeders and 46 (31.30%) were obtained from other sources. There was a statistically significant difference (p<0.001) in the rate of noise-related fears between the dogs directly purchased from breeders and dogs obtained from other sources.